Ecological Forecasting for Night Monkeys in the Aotus lemurinus Complex: Climate‑driven Threats to Habitat Suitability (2025)
ABSTRACT: Climate change poses threats to global biodiversity, particularly in groups such as American primates, which are restricted to forested ecosystems. Assessing species-specific and habitat vulnerabilities is crucial to understand how climate change impacts this group. We investigated the impact of climate change and habitat vulnerability for the three species of night monkeys in the Aotus lemurinus complex (A. grisemembra, A. lemurinus, and A. zonalis), a group of American primates which is highly vulnerable to environmental disturbance. Using ecological niche modeling, we projected how different climate scenarios could alter the distribution of the three species, and calculated a vulnerability transformation index for quantifying susceptibility of natural habitats to conversion into anthropogenic land covers. Our findings reveal that the currently most favourable habitats for all species will reduce, with A. griseimembra experiencing the greatest declines, particularly in lowland areas. A. lemurinus shows relatively smaller habitat losses overall, with the greatest reduction in Ecuador. A. zonalis is the least-affected species, but still faces some level of risk. The results emphasize the need for detailed ecological assessments in biogeographically important regions, particularly areas projected to maintain habitat stability under future climate scenarios. Targeted research should focus on identifying species-specific responses to habitat changes in order to refine conservation strategies for night monkeys. These findings provide actionable insights for prioritizing highland forest restoration, implementing mitigation measures for habitat loss driven by human activities and climate change, and enhancing monitoring in underexplored regions.